Sistem Pengembangan Asuransi Usaha Ternak Sapi/Kerbau di Provinsi Aceh - Rahmat Fadhil; Zuraida Hanum; Muhammad Yunus (Jurnal Ilmu Pertanian Indonesia, 2021)
Cow/buffalo-business insurance (AUTS/K) is a form of risk mitigation for livestock businesses run by farmers. Various risks that are often occurred include livestock death, natural disasters, disease outbreaks, and livestock theft. If not handled properly, it can threaten the sustainability of this business, especially the small-scale livestock-business sector. This study aimed to formulate a developing system of cattle/buffalo-livestock insurance using the soft-systems methodology (SSM) approach. This research was conducted in Aceh Province from December 2020 to February 2021 using an expert survey by collecting data and information through parties who have competence or expertise in the field being studied. The development of this insurance system can be said to be an effort to improve and a solution to any problems currently being experienced in the implementation of AUTS/K. The result of improvements includes optimizing the roles of each party involved and program innovation to intensify AUTS/K products among breeders. The results showed that the SSM approach could describe the problem well and form a conceptual model for the AUTS/K system in Aceh province. Improvements to policies, assistance, and promotion systems are recommended as solutions to the problems related to livestock-insurance system implemented. Keywords: breeders, conceptual model, insurance system, soft-systems methodology, syariah insurance